Remote Experimentation Network: an Inter-University Peer-to-Peer e-Service - Alves, Gustavo R. (2017)
The goal of this presentation is to discuss the benefits and challenges of yielding an inter-continental network of remote laboratories supported and used by both European and Latin American Institutions of Higher Education.